2016
DOI: 10.1016/j.immuni.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Mechanisms to Immune-Checkpoint Blockade in Cancer: Tumor-Intrinsic and -Extrinsic Factors

Abstract: Inhibition of immune regulatory checkpoints, such as CTLA-4 and the PD-1-PD-L1 axis, is at the forefront of immunotherapy for cancers of various histological types. However, such immunotherapies fail to control neoplasia in a significant proportion of patients. Here, we review how a range of cancer-cell-autonomous cues, tumor-microenvironmental factors, and host-related influences might account for the heterogeneous responses and failures often encountered during therapies using immune-checkpoint blockade. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
691
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 867 publications
(699 citation statements)
references
References 166 publications
(182 reference statements)
7
691
0
1
Order By: Relevance
“…While PD-1 inhibition represents a major advance in the treatment of melanoma and other cancers, it is well recognized that in most cancers only a minority of patients benefit from this approach (3,4,25), and that host and tumor factors play a role in response to these agents (11,15,17). Previously, we studied the abundance of tumor-infiltrating peCTLs in freshly isolated melanoma tumors using a novel assay that uses multiparameter flow cytometry and found that the fraction of peCTL/total CD8 + T cells within tumors directly correlated with response to anti-PD-1 monotherapy in a 40-patient cohort (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While PD-1 inhibition represents a major advance in the treatment of melanoma and other cancers, it is well recognized that in most cancers only a minority of patients benefit from this approach (3,4,25), and that host and tumor factors play a role in response to these agents (11,15,17). Previously, we studied the abundance of tumor-infiltrating peCTLs in freshly isolated melanoma tumors using a novel assay that uses multiparameter flow cytometry and found that the fraction of peCTL/total CD8 + T cells within tumors directly correlated with response to anti-PD-1 monotherapy in a 40-patient cohort (18).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include tumor mutation burden (6)(7)(8), host microbiome (9, 10), disease stage (11), lactate dehydrogenase (LDH) levels (11), baseline tumor size (11), and the presence of liver metastasis (12)(13)(14). These factors have been referred to as the cancer immunogram (15) or the cancer immune set point (16), and include both tumor intrinsic and extrinsic factors (17).…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-mediated blockade of immune-checkpoint receptors is now clinically approved across a range of indications, 1 however such treatments lack sustained efficacy in the majority of patients. 2 Thus, a deeper understanding of therapeutic interventions represents an area of unmet clinical need. Given that redundancy may exist between immunosuppressive mechanisms utilized by a tumour, there is great scope to improve clinical responses by combining existing immune-targeting and/or tumour targeting therapies in a rational manner.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, not only do the tumor and its microenvironment seem to influence the response to immunotherapy, but so do host-related factors like age, HLA, diet, metabolism, infections and microbiome (recently revised by Pitt et al). 13 The increased complexity generated by the genetic, immune and host related heterogeneity represents a challenge for the identification of the optimal treatment combination. Ideally, various steps of the immune response would be therapeutically modulated in association with current therapies, creating a large panel of possibilities.…”
Section: Introductionmentioning
confidence: 99%